2020
DOI: 10.2196/17597
|View full text |Cite
|
Sign up to set email alerts
|

Once Daily Versus Overnight and Symptom Versus Physiological Monitoring to Detect Exacerbations of Chronic Obstructive Pulmonary Disease: Pilot Randomized Controlled Trial

Abstract: CONSORT 2010 checklist of information to include when reporting a randomised trial* Section/Topic Item No Checklist item Reported on page No Title and abstract 1 a I d e n t i f i c a t i o n a s a r a n d o m i s e d t r i a l i n t h e t i t le 1b Structured summary of trial design, methods, results, and conclusions (for specific guidance see CONSORT for abstracts)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…It is known that decompensated hypercapnic respiratory failure is associated with increased mortality (34), which is reduced by non-invasive ventilation (NIV) (34,54). While expert societies recommend titrating supplemental oxygen during ECOPD to SaO 2 of 88-92% (7,55), studies of ECOPD suggest the average reduction in SaO 2 was not more than 2% (56,57). Based on this evidence, the panel agreed that when change from baseline is known, a mild ECOPD would be characterized by an arterial oxygen saturation (SaO 2 ) ≥92% and a change ≤3%, a moderate event would be SaO 2 <92% and/or a change >3%, and a severe event by acidotic hypercapnic respiratory failure, i.e., arterial partial pressure of carbon dioxide (PaCO 2 ) >45 mmHg and pH <7.…”
Section: Hypoxemia and Hypercapniamentioning
confidence: 99%
“…It is known that decompensated hypercapnic respiratory failure is associated with increased mortality (34), which is reduced by non-invasive ventilation (NIV) (34,54). While expert societies recommend titrating supplemental oxygen during ECOPD to SaO 2 of 88-92% (7,55), studies of ECOPD suggest the average reduction in SaO 2 was not more than 2% (56,57). Based on this evidence, the panel agreed that when change from baseline is known, a mild ECOPD would be characterized by an arterial oxygen saturation (SaO 2 ) ≥92% and a change ≤3%, a moderate event would be SaO 2 <92% and/or a change >3%, and a severe event by acidotic hypercapnic respiratory failure, i.e., arterial partial pressure of carbon dioxide (PaCO 2 ) >45 mmHg and pH <7.…”
Section: Hypoxemia and Hypercapniamentioning
confidence: 99%
“…It has been demonstrated that early detection of exacerbations in Chronic Obstructive Pulmonary Disease (COPD) speeds recovery time [26,27]. Home monitoring has thus been recommended in lung diseases such as COPD to support earlier detection of exacerbation [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The test data have been processed and are ready to feed into the algorithm. Currently, algorithm development is in progress, and we are using analyses from a priori data sets [ 13 ] and results from similar studies to inform the design of our algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [ 12 , 13 ] on exacerbations in COPD found that changes in resting heart rate (RHR), pulse oxygen saturation (SpO 2 ), and peak airflow are highly correlated with symptoms before, during, and after exacerbation onset, as shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation